Effect of Dietary Inclusion of Citric Acid with Phytase as Supplement on Growth Responses of Rainbow Trout - Suraj Kumar Singh; Mahendra Prasad Bhandari; Prem Timalsina (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Rainbow trout, a salmonid species has an economic importance worldwide and contributes to the indigenous food security. The present study was conducted in complete randomized design (CRD) to evaluate the dietary inclusion of citric acid with phytase as supplement on growth responses of rainbow trout. There were four treatments of diets with 0.5% citric acid (T1), 1% citric acid (T2), 1.5% citric acid (T3) and 0% control (T4) of citric acid incorporated with 1200FYT phytase as supplement. The treatments were replicated three times. Total harvest weight of fish in T3 (5720.2±105.6g) was significantly higher and different than T2 (4595.9±434.9g), T1 (4589.8±240.2g) and T4 (4567.5±217.3g). The highest daily growth rate was seen in treatment T3 (1.1±0.0) which was significantly different than T2 (0.9±0.0), T1 (0.9±0.0) and T4 (0.8±0.0). The highest specific growth rate was seen in the treatment T3 (0.8±0.01) which was significantly different than T1 (0.7±0.0), T2 (0.7±0.1) and T4 (0.7±0.0). The lowest food conversion ratio was seen in T3 (2.2±0.1) which was significantly different with T2 (2.6±0.1), T1 (2.7±0.1) and T4 (2.8±0.1). Similarly, the highest protein efficiency ratio was seen in treatment T3 (1.0±0.1) which was not significantly different with T2 (0.8±0.0) and T1 (0.8±0.1) but was significantly different than T4 (0.7±0.0). No significant changes were observed in water temperature, dissolve oxygen and pH under different treatments. The present findings demonstrated that dietary inclusion of citric acid with phytase as supplement enhance growth by reducing the pH in the gut which increases the phytate hydrolysis, kills the pathogens, decreases the rate of gastric emptying, improves mineralization and nutrient absorption.